HYPOTHYROÏDIE AUTO-IMMUNE REVELEE PAR UNE GALACTORRHEE A COTONOU - WANVOEGBE, Armand Finangnon; AGBODANDE, KOUESSI ANTHELME; OGOUDJOBI, OGOURINDÉ MATHIEU (My University, 2018)
La galactorrhée est l’un des signes révélateurs de l’hyperprolactinémie dont les étiologies sont mul-tiples et variées. Si certaines de ces étiologies sont fréquemment retrouvées, d’autres par contre, telle que l’hypothyroïdie frustre semblent être rares. Nous rapportons ici un cas d’hypothyroïdie frustre auto-immune révélée par une hyperprolactinémie symptomatique qui a été traitée exclusivement avec succès par une hormonothérapie substitutive. Mots clés : Hypothyroïdie, hyperprolactinémie, galactorrhée, troubles menstruels ABSTRACT Autoimmune hypothyroidism revealed by galactorrhea in Cotonou Galactorrhea is one of the revealing signs of hyperprolactinemia which has multiple and varied caus-es. Although some of these causes are frequently found those such as subclinical hypothyroidism may appear to be rare. We report here a case of autoimmune subclinical hypothyroidism revealed by symp-tomatic hyperprolactinemia which has been treated exclusively and successfully with hormone re-placement therapy.
Keywords: Hypothyroidism; hyperprolactinemia; galactorrhea; menstrual disturbancies